Speculative Devices for Photo Display - Durrant, Abigail; Taylor, Alex; Taylor, Stuart; Molloy, Mike; Sellen, Abigail; Frohlich, David; Gosset, Phil; Swan, Laurel (CHI '08 extended abstracts on Human factors in computing systems, 2008)
In this paper, we describe three purposefully provocative, digital photo display technologies designed for home settings. The three devices have been built to provoke questions around how digital photographs might be seen and interacted with in novel ways. They are also intended for speculation about the expressive resources afforded by digital technologies for displaying photos. It is hoped interactions with the devices will help researchers and designers reflect on new design possibilities. The devices are also being deployed as part of ongoing home-oriented field research.